The integration of yoga into occupational therapy practice for people with multiple sclerosis - Candray, Haylee A., author; Schmid, Arlene A., advisor; Atler, Karen E., committee member; Fling, Brett W., committee member (Colorado State University. Libraries, 2020)
The purpose of this study was to fill a research gap, by providing initial insight into the use of yoga in occupational therapy practice (OT) for people with multiple sclerosis (PwMS). More specifically, this study aimed to answer how and why occupational therapists (OTs) integrate yoga into clinical practice for PwMS. Eight OTs, residing across the United States, completed an online survey and semi-structured telephone interview. Telephone interviews were transcribed verbatim and inductively open coded. Themes, answering the questions of how and why OTs use yoga for PwMS, emerged through thematic data analysis including: (1) OT and yoga are a natural and complementary fit; (2) holistic benefits for clients beyond therapy; (3) leveraging personal ties to yoga; and (4) use of yoga is dependent on client factors and clinical environment. Since OTs use activities to promote health and well-being, yoga may be appropriate for PwMS because its use is context- and client-centered and allows for shared engagement in a meaningful activity for clients and therapists. Furthermore, as yoga and OT together are a natural and complementary fit, OTs use of yoga may be holistically beneficial to PwMS during and after being discharged from occupational therapy. Future research needs to establish the efficacy of integrating yoga into clinical OT practice as well as qualitatively assess PwMS' experience of engaging in yoga during occupational therapy.
Keywords: multiple sclerosis; OT; MS; yoga; occupational therapy